Perilaku Masyarakat Dalam Pengelolaan Keuangan Melalui Bank Keliling : Bagaimana Peran Pemerintah - Tyo Rizky Siagian; Tri Inda Fadhila Rahma; Sugianto Sugianto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – The demand for credit services in Parbarakan Village has increased significantly every year. This increase is generally driven by various factors, especially the socio-economic conditions of the community, such as insufficient income to meet the needs of life, both basic needs and urgent needs. This condition encourages many housewives to apply for loans as an effort to cover the lack of funds. The majority of people who work as farmers with unstable incomes also strengthen the need for loans. This situation is then exploited by certain parties from outside by providing massive loan offers, thus encouraging an increase in demand. Objective – To find out the role of the Perbarakan village government in resolving the problem of mobile banking services among the community. Design/ methodology/ approach – This study uses a qualitative phenomenological approach. Where primary data is obtained by observing and interviewing mobile bank officers and customers using mobile bank services. Secondary data is obtained from websites, literature studies that support research and various other sources. Data collection techniques in this study were carried out in several ways, namely by field observation, data obtained through this observation are the main data collected directly in the field. Interviews to obtain data directly, researchers conducted interviews with informants who were given a series of questions. Findings – the role of the government in solving the problem of mobile banks in Perbarakan village is that the village government creates its own bank through BUMDES with the hope that the people of Perbarakan village can be helped with capital loans offered by the government with very small interest so as not to burden the people of Perbarakan village. Creating training for young people and housewives, the purpose of holding training by BUMDes is also part of the process of absorbing community aspirations that may have rarely been touched by the village. One of them is sewing course training. In Perbarakan village, the majority of housewives have sewing skills to be able to maximize this, BUMDes must create a convection company where the company can sell sewing works from housewives in Perbarakan village. As the results of the interview conducted with the head of Perbarakan village who stated that in our village there are always sewing courses for mothers, the hope is that sewing courses in our village can be additional income for mothers in our village and hopefully it can reduce the community’s dependence on this mobile bank. Implications – This study reveals the reasons why people choose to use mobile banks, then with this study can find the factors that cause people to borrow from mobile banks and what they are used for and this study reveals what risks people face when choosing to use the services of mobile banks. And this study also explains how the role of the village government is in solving the problems of people who use mobile bank services in Perbarakan village. Research Limitations – This research focuses on the impact of the existence of mobile banks in Perbarakan village and how the government’s efforts are to reduce people’s sense of dependence on using mobile banking services.